PENGEMBANGAN VIDEO ANIMASI BERBASIS POWTOON PADA MATERI EKOSISTEM SISWA KELAS IV SD NEGERI 56 KOTA TERNATE - Anriyani A Basahona; Pamuti Pamuti; Wawan S Nadra (PEDAGOGIK, 2023)
The aims of this study were (1) to determine the development of Powtoon-based animated video media on ecosystem material for fifth grade students of SD Negeri 54 Ternate City to meet valid criteria (2) to determine the development of Powtoon-based animated video media on ecosystem material for fifth grade elementary school students Negeri 54 Kota Ternate can meet practical criteria (3) to find out the effectiveness of developing Powtoon-based animated video media on ecosystem material to improve learning outcomes for class V students at SD Negeri 54 Kota Ternate.This research is research and development (RD) using the Borg and Gall development model modified by Sugiyono (2007) consisting of ten steps and this research is limited to the sixth step namely potentials and problems, data collection, product design, design validation, design revision , and product trials. The validators who validated the development of Powtoon-based animated video media were media experts, science subject matter experts, media practicality experts by teachers and student responses. This data collection technique is through a feasibility validation instrument for Powtoon-based animated video media on ecosystem material using interviews, questionnaires, test questions, and documentation. The data analysis technique uses a quantitative descriptive technique. The research results show that; The development of Powtoon-based animated video media on ecosystem materials obtained an average score of 93% from both expert lecturers and the media was declared very valid, feasible to use; animated video media based on Powtoon on ecosystem material is stated to be very practical and feasible to use in the learning process which gets an average score of 87%, this value is obtained from a teacher's questionnaire and student responses; Powtoon-based animated video media on ecosystem material was declared effective which was obtained from the average posttest score of 89 from KKM ≥70 and from a total of 18 students. With this it can be concluded that the development of Powtoon-based animated video media on ecosystem material for Grade V Students of SD Negeri 54 Ternate City can be stated as media that meets the criteria of being valid, practical, and effective for use in the learning process by teachers and students.